A Systematic Study of Electrolyte Additives in Single Crystal and Bimodal LiNi0.8Mn0.1 Co0.1O2/Graphite Pouch Cells. Issue 9 (6th September 2021) - Song, Wentao; Harlow, Jessie; Logan, Eric; Hebecker, Helena; Coon, Matthew; Molino, Laurent; Johnson, Michel; Dahn, Jeff; Metzger, Michael
Abstract : A few weight percent of electrolyte additives can dramatically improve Li-ion battery performance and lifetime. A systematic investigation of a series of electrolyte additive formulations was performed on bimodal (BM) and single crystal (SC) LiNi0.8 Mn0.1 Co0.1 O2 (NMC811)/artificial graphite (AG) pouch cells. Long-term cycling tests at different temperatures (20 °C, 40 °C, and 55 °C) and different upper cutoff voltages (4.06 V and 4.20 V) were performed. These tests results were combined with advanced characterization techniques like ultra-high precision charging (UHPC), ex-situ gas measurement, and automatic cell storage tests to rank the additives based on their effectiveness. Radar plots and a figure-of-merit (FOM) approach were further utilized to summarize results for the BM and SC NMC811/AG cells. This work provides a useful benchmark for those developing NMC811/graphite cells and gives important insights for future electrolyte additive studies.